Understanding religious fundamentalists an introduction - Herriot, Peter 1939- (Routledge, 2024)
"This book introduces the prominent role that fundamentalists play in religious, cultural, and political arenas. It begins by investigating religious fundamentalist groups and their psychological motivations for this counter-cultural adherence. Subsequent chapters explore how fundamentalisms meet universal psychological needs for meaning, identity, agency, and self-esteem. Moving from individual psychology to social context, the latter half of the book explores how fundamentalist movements derive and exercise their authority and how leaders may strategise to appeal to external societies. The closing chapters seek to place the growth of fundamentalisms and their continued popularity in the social context of modernity and populism. With engaging discussion questions and suggestions for further reading, this book is ideal for students of social science and religion, as well as readers interested in the psychological roots of fundamentalism"--
Keywords: Religious fundamentalism; Christian leadership; Religion and sociology; Intégrisme; Leadership chrétien; Sociologie religieuse; sociology of religion; Einführung